REFLEKSI FILOSOFIS ATAS PENGEMBANGAN CIVIC VALUES MELALUI PEMBERDAYAAN EKONOMI MASYARAKAT BERSAMA PESANTREN - Alim Roswantoro (Millah: Journal of Religious Studies, 2011)
The article is the philosophical reflection on the result of the qualitative research of the two pesantren in Java, i.e., Pesantren Tarbiyatun Nasyi’in Paculgowang Jombang at East Java and Pesantren Al-Hikmah Karangmojo at Gunung Kidul Yogyakarta. The two pesantren were chosen because they have gotten the empowering training from one of the centers of Sunan Kalijaga State Islamic University. The main target of the training is to develop civic values, that is, democracy, pluralism and gender equality in pesantren and the surrounding society through the acitivities of economic empowerment of society in cooperation with pesantren. The article tries to explore and find out the results of the empowerment of the two pesantrens, and then tries to reflect them philosophically. And the main result is that the pesantrens and the surrounding peoples can accept the importance of the values of democracy, pluralism, and woman-man equality easier through the real economic activities rather than through discussion on those values in the Islamic perspective. The article can philosophically reflects that the endeavor to change the peoples’ mindset will become nothing if we do not give them the basic need for being able to survive economically. The welfare equality lead them to easily understand what the value of mutual respect making all people free.